International economic law in the era of datafication / Shin-Yi Peng, National Tsing Hua University. - Peng, Shin-Yi (Cambridge international trade and economic law., 2024)
This book addresses the challenges of datafication through the lens of international economic law. We are undergoing a wave of datafication practices. If such practices simply continue to evolve without being examined and repaired along the existing path of development, the same issues will continue to accumulate and will more than likely be amplified. The unprecedented economic and social influence of big tech has served as the catalyst for the concept of 'digital sovereignty,' which is rooted in the need to safeguard regulatory autonomy in a datafied world. The current wave of data-driven innovations has placed the policy debates on digital trade and data governance into an even more challenging context. The book - whose chapters are connected by the many facets of 'data' - systematically explains how international economic law can reduce the perils of datafication instead of enhancing them. This title is part of the Flip it Open Programme and may also be available Open Access. Check our website Cambridge Core for details.